Fetal Diagnosis of Left Ventricular Aneurysm: A Case Report - Lauren Giacobbe; Preston Williams; Kirk Ramin; Shanthi Sivanandam (Thieme Medical Publishers, Inc., 2011)
Congenital left ventricular aneurysm is a rare but potentially lethal condition. We describe a case of isolated congenital left ventricular aneurysm diagnosed at 28 weeks' gestation. In addition to standard imaging, we utilized color-coded transthoracic tissue Doppler techniques to further evaluate the aneurysm postnatally.